Russia's Hero Cities : From Postwar Ruins to the Soviet Heroarchy - Mijnssen, Ivo (Indiana University Press, 2021)
By exploring the significance of Hero Cities in Soviet identity and the enduring but conflicted importance they hold for Russians today, Russia's Hero Cities exposes how the Great Patriotic War no longer has the power to mask the deep rifts still present in Russian society.